2013
DOI: 10.1021/jp404179x
|View full text |Cite
|
Sign up to set email alerts
|

High Lithium Ion Electroinsertion Rate into Self-Assembled Films Formed from TiO2

Abstract: We prepared self-assembled materials consisting of TiO 2 nanoparticles, N,O-carboxymethylchitosan (NOCMCh), and poly(ethylene oxide) (PEO) by the layer-by-layer (LbL) technique, aiming to employ them as modified electrodes under high lithium ion electroinsertion rate. Electrostatic interaction between the components promoted growth of visually uniform TiO 2 /NOCMCh films with highly controlled thickness. We used NOCMCh to produce a polymeric mixture with PEO to incorporate the polyether into the self-assembled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…To solve its intrinsic disadvantage, different strategies have been devoted to improve the lithium ion storage performance, such as compounding with conductive agents to enhance electronic conductivity (Gomes et al, 2013;Wang et al, 2016), reducing particle size to nano-scale to shorten the lithium ion diffusion distance (Hu et al, 2015), and manufacturing mesoporous or porous TiO 2 to increase the electrolyte/electrode contact area (Li et al, 2015. Furthermore, researchers found that the electrical property of TiO 2 is impressible to aliovalent ions doping in the lattice (Zhang et al, 2012;Zhao et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…To solve its intrinsic disadvantage, different strategies have been devoted to improve the lithium ion storage performance, such as compounding with conductive agents to enhance electronic conductivity (Gomes et al, 2013;Wang et al, 2016), reducing particle size to nano-scale to shorten the lithium ion diffusion distance (Hu et al, 2015), and manufacturing mesoporous or porous TiO 2 to increase the electrolyte/electrode contact area (Li et al, 2015. Furthermore, researchers found that the electrical property of TiO 2 is impressible to aliovalent ions doping in the lattice (Zhang et al, 2012;Zhao et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Among these materials, tungsten(VI) oxide (WO 3 ) is a particular metal oxide which can offer a wide range of technological applications. energy storage, electrochromic devices, etc.…”
Section: Introductionmentioning
confidence: 99%
“…has become a subject of growing interest. [1][2][3][4] Among these materials, tungsten(VI) oxide (WO 3 ) is a particular metal oxide which can offer a wide range of technological applications. It is a representative metal oxide of a group of chromogenic materials due to the coloration effects associated with various processes.…”
Section: Introductionmentioning
confidence: 99%
“…The rate of insertion, and therefore the diffusion coefficient of metal ions in the electrode material, is one of the important evaluation parameters for fast charging and discharging metal ion battery. For determining diffusion coefficient of Lithium in the solid state electrode materials, electrochemical methods such as Electrochemical Impedance Spectroscopy (EIS), [26,27] Galvanostatic Intermittent Titration Technique (GITT), [26,28] Potentiostatic Intermittent Titration Technique (PITT) [29–33] and Cyclic Voltammetry (CV) [34,35] have been applied.…”
Section: Introductionmentioning
confidence: 99%